2017
DOI: 10.1186/s13065-017-0338-5
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide-based diamides derivatives as potential cytotoxic agents: synthesis and biological evaluation

Abstract: A series of diamides derivatives containing nicotinamide unit were designed, synthesized and evaluated for their potential cytotoxic activities against human cancer cell lines. All the synthesized compounds were characterized using spectroscopic methods mainly including 1H NMR, 13C NMR and MS. The bio-evaluation results indicated that some of the obtained compounds (such as 4d, 4h, 4i) exhibited good to moderate cytotoxic effects on lung cancer cell lines (NCI-H460, A549, and NCI-H1975), especially, compound 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Due to the appreciable stability with time of the complex in DMSO under physiological-like conditions, the complex could be evaluated as potential cytotoxic agent. Previously, many studies were reported the cytotoxicity properties of NA [67][68][69][70]. Hence, the cytotoxicity of the BBHMP and its platinum(II) complex was examined for human prostate (DU145) and breast (MCF7) cancer cell lines with an MTT assay.…”
Section: Cytotoxicity Resultsmentioning
confidence: 99%
“…Due to the appreciable stability with time of the complex in DMSO under physiological-like conditions, the complex could be evaluated as potential cytotoxic agent. Previously, many studies were reported the cytotoxicity properties of NA [67][68][69][70]. Hence, the cytotoxicity of the BBHMP and its platinum(II) complex was examined for human prostate (DU145) and breast (MCF7) cancer cell lines with an MTT assay.…”
Section: Cytotoxicity Resultsmentioning
confidence: 99%
“…Amide protons were identified between 8.7 ppm and 8.3 ppm in all compounds. 16 Similarly triplet and doublet protons of compound 3 vanished in compound 4. This absent confirmed the ester hydrolyzed product (4).…”
Section: Preparation Of N-substituted-2-(nicotinamido) Thiazole-4-carboxamide (5a-i)mentioning
confidence: 94%
“…Recently, during the course of our research on discovery of functional molecules, a series of diamides derivatives bearing nicotinamide unit were obtained ( Peng et al, 2017 ), and an interesting phenomenon was found based on the preliminary results. All of the similar diamides without nicotinamide moiety lost the inhibitory activity except the compound bearing diarylamine unit ( A2 , R = Me), and this compound exhibited good cytotoxic activity against the tested lung cancer cell lines (NCI-H460, A549, and NCI-H1975) with IC 50 values of 14.66–46.42 μM ( Figure 2 ).…”
Section: Introductionmentioning
confidence: 99%